Effect of bore fluid and post treatment on polyethersulfone ultrafiltration hollow fiber membrane - Lee, Sze Yean (2008)
Polyesthersulfone (PES) hollow fiber membranes were prepared via the phase inversion process from dope solution containing PES, n-methylpyrrolidone (NMP), and polyvinylpyrrolidone (PVP). The effect of bore fluid flow rate (BFR) and bore fluid composition (BFC) on the morphology, permeability and separation performance of the spun UF membranes has been investigated. The influence of hypochlorite and microwave irradiation post treatment method was compared. Dry jet wet spinning process was the method chosen to fabricate the hollow fibers with an air gap of 10 cm. Water was used as external coagulant and the temperature was maintained at 14Â° Celsius. Solute separation experiments were conducted using polyethylene glycol. It was found that when the BFR is increased from 1.0 ml/min to 3.5 ml/min, the pure water permeation fluxes (PWP) increased from 0.14 L/ (m2.h.bar) to 1.29 L/ (m2.h.bar). The rejection rate of PEG decreased when BFR increased for all PEG solutions respectively. Characteristics of membranes using transport data revealed that the pore size of UF membranes increases as BFR increases. Experimental results also illustrated that PWP flux of the PES hollow fibers membranes spun with different percentage of NMP in its bore fluid slowly increases as the content increased from 20% NMP to 60% NMP but its rejection rate is decreased. The increasing solvent content in the bore fluid reduced the water activity and hence promoted the delayed demixing process during the membrane formation. Experimental results also revealed that the microwave post treatment produced membranes with better separation performance (approximately 10% higher) with smaller pore diameters in comparison to those post-treated with hypochlorite.